How do central bank collateral frameworks affect non-financial firms? - Matthias Kaldorf; Florian Wicknig (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Central banks implement monetary policy by extending credit to banks, for example via standing facilities or long-term refinancing operations. In addition to setting policy rates, central banks also specify in their collateral framework which financial assets banks can pledge to obtain central bank funding. Here we discuss the design of collateral frameworks for the case of corporate sector assets. This is particularly relevant in countries where the supply of safe government bonds is insufficient to satiate collateral demand.
Keywords: 330